Evaluation of the productivity of thirteen buffel grass cultivars in the semi-arid region of Pernambuco, Brazil - Silva, Célia Maria M. de S.; Oliveira, Martiniano C. de; Albuquerque, Severino G. de (Pesquisa Agropecuaria Brasileira, 2014)
An experiment to identify cultivars of buffel grass (Cenchrus ciliaris L.) well adapted to the semi-arid conditions of Northeast Brazil, was conducted from 1979 to 1983, at the Caatinga Experimental Field, of the Centro de Pesquisa Agropecuária do Trópico Semi-Árido (EMBRAPA/CPATSA). in Petrolina, Pernambuco State, Brazil. Thirteen cultivars of buffel grass, vegetatively established in 4 m x 2.5 m plots, were evaluated. The experimental design was randomized complete blocks with five replications. Among the highest cultivars, the cv. Molopo was the best one, 6,750 kg of dry matter/ ha-year, 106 cm height and good foliage Comparatively, the cv. Biloela, the most used at CPATSA, was short (97 cm) and less productive (5,355 kg of dry matter/ha-year). Among the cultivars of mean height, Gayndah was the shortest (77 cm) and F1 Hibrid 171 was the least productive (3,745 kg of dry matter/ha-year). Related to the nutritive value, expressed in crude protein in the dry matter, Gayndah and Molopo were the highest and the lowest, showing 12.43% and 9.51%, respectively.